A Model for Mobile Learning Integration in Higher Education Based on Students’ Expectations - Todoranova, Latinka Ivanova; Nacheva, Radka Valerieva; Sulov, Vladimir Stoyanov; Penchev, Bonimir Penchev (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Mobile learning can be identified as the next stage in the development of e-learning. In this regard, the purpose of this paper is to propose a model for mobile learning integration in higher education which is based on analysis of students’ expectations. То achieve this goal, a survey has been conducted among students enrolled in programs in the field of information and communication technologies. The analysis of the collected data shows that students have mobile devices, which they use not only for communication on social networks, but also for education. In addition, their expectations regarding mobile learning have been identified taking into account their study program and their previous experience with an e-learning platform.